Study on the impact of A-H connectivity mechanism on financial market - Cao Qi (SHS Web of Conferences, 2025)
The Stock Connect program remains a foundational initiative as China moves to liberalize its financial markets, demonstrating its commitment to gradually opening up its markets while maintaining regulation. Its success has paved the way for other cross-border initiatives to further integrate the Chinese market with the global financial system. This study aims to analyze the Current State of A-H Stock Connect and limitations, and explore the impact of A-H Stock Connect on financial markets. The study found that A-H Stock Connect has transformed China’s capital markets in several ways： increased the investor base, increased liquidity, increased cross-border capital flows, decreased valuation disparities, and sparked financial innovation. The recent years have witnessed a spurt of progress in A-H stock. The prospect of A-H stock remains strong and promising to promote China’s economy. This study could help individuals understand how A-H Stock work and its impacts, to better make use of A-H stock.